Synthesis, Characterization and Breast Anti-cancer Activity of Iron(II), Cobalt(II), Nickel(II) and Copper(II) Complexes with a Hexadentate Schiff Base Ligand Derived from 2,5-Dihydroxy-1,4-benzoquinone with 5-Amino-2-methylphenol - Riyam Baqer Ibrahim; Suad Taha Saad (Universitas Gadjah Mada, 2023)
The complexes of Fe(II), Co(II), Ni(II), and Cu(II) Schiff base ligand derived from 2,5-dihydroxy-1,4-benzoquinone and 5-amino-2-methylphenol were synthesized. The ligand was synthesized by the reaction between the mentioned ketone and amine in 1:2 molar ratio, respectively. The four metal complexes were synthesized by refluxing the ligand with the related metal(II) chloride salts. The synthesized compounds were characterized using FTIR spectroscopy, UV-visible, 1H-NMR, conductivity, atomic absorption, magnetic susceptibility, and thermogravimetric analysis. According to the results, the chelation between metals and ligand occurs with the imine groups and the deprotonated hydroxyl groups of 2,5-dihydroxy-1,4-benzoquinone and 5-amino-2-methylphenol in the ligand. The conductivity test of the four complexes shows the non-electrolytic nature of them. The magnetic susceptibility values of Fe(II), Co(II), Ni(II), and Cu(II) complexes are 4.20, 4.11, 2.97, and 2.34 B.M, respectively. The thermogravimetric and atomic absorption analyses suggest the general chemical formula for the complexes is [M2(L)(H2O)6]. In addition, the ligand and one of its metal complexes (Co(II) complex) were examined against breast cancer cells, and they gave the IC50 of 101.24 and 129.2 µg/mL, respectively. This result suggests that Co(II) complex is a better anti-cancer agent in comparison with the ligand.